Risk and Causes of Death in Patients After Alcohol Septal Ablation for Hypertrophic Obstructive Cardiomyopathy - Veselka, Josef; Zemánek, David; Jahnlová, Denisa; Krejčí, Jan; Januška, Jaroslav; Dabrowski, Maciej; Bartel, Thomas; Tomašov, Pavol (The Canadian journal of cardiology, 2015)
BACKGROUND: Because the final myocardial scar might be theoretically associated with an increased risk of sudden cardiac death, the long-term clinical course of patients who undergo alcohol septal ablation (ASA) is still a matter of debate. In this retrospective multicentre study, we report outcomes after ASA, including survival, analysis of causes of deaths, and association between time and cause of death. METHODS: We enrolled 366 consecutive patients (58 ± 12 years, 54% women) who were treated using ASA and followed-up for 5.1 ± 4.5 years. RESULTS: The in-hospital and 30-day mortality were 0.5% and 0.8%, respectively; the ASA-related morbidity was < 20%. Overall, 52 patients died during 1867 patient-years, which means the all-cause mortality rate was 2.8% per year. The mortality rates of sudden death and sudden death with an appropriate implantable cardioverter-defibrillator (ICD) discharge were 0.4% and 1% per year, respectively. Patients with sudden death or appropriate ICD discharge experienced these mortality events at younger age than patients who died of other hypertrophic obstructive cardiomyopathy-related causes (60.8 years [range, 52-71.5 years] vs 72.4 years [range, 64.2-75.2 years]; P = 0.048). A total of 292 patients (80%) had an outflow gradient ≤ 30 mm Hg, and 327 patients (89%) were in New York Heart Association class ≤ II at the last clinical check-up. CONCLUSIONS: ASA had low procedure-related mortality, with subsequent 1% occurrence of sudden mortality events per year and 2.8% mortality rate per year in the long-term follow-up. Patients with sudden death or ICD discharge experienced the mortality events approximately 1 decade earlier than patients who died from other causes not related to hypertrophic cardiomyopathy.
Keywords: Defibrillators, Implantable; Poland; Cicatrix; Hospital Mortality; jizva; Humans; následné studie; Rakousko; myokard; lidé středního věku; Middle Aged; sklerotizující roztoky; Czech Republic; mortalita v nemocnicích; Time Factors; Alcohols; Follow-Up Studies; mužské pohlaví; příčina smrti; defibrilátory implantabilní; Česká republika; Austria; Polsko; katetrizační ablace; alkoholy; časové faktory; Cardiomyopathy, Hypertrophic; ženské pohlaví; Catheter Ablation; Electric Countershock; Sclerosing Solutions; náhlá srdeční smrt; elektrická defibrilace; Death, Sudden, Cardiac; lidé; hypertrofická kardiomyopatie; analýza přežití; Aged; Myocardium; senioři; Male; Cause of Death; Survival Analysis; Female